Strengthening Students' Scientific Literacy through the Ilmi Interpretation Approach in Islamic Religious Education in Elementary Schools - Anam, Muhammad Abdul; Anwar, Khairil; Warman, Taufik (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
The low level of scientific literacy among elementary school students in Indonesia underscores the need for learning innovations that integrate scientific knowledge with religious contexts relevant to students’ lives. In Islamic Religious Education (IRE) lessons, verses about nature have great potential to develop scientific thinking skills, but this potential has not been fully utilized. This study aims to examine how the scientific interpretation approach can strengthen elementary school students' scientific literacy by systematically linking Qur’anic verses to natural phenomena. The study used a qualitative case study design across four elementary schools in Pulang Pisau Regency. Data were collected through learning observations, in-depth interviews with teachers and students, and the analysis of documents, including lesson plans and learning outcomes. The analysis was conducted using the interactive model of Miles, Huberman, and Saldaña with triangulation of sources and techniques to ensure data validity. The results of the study indicate that the scientific interpretation approach improves students’ ability to ask scientific questions, explain evidence-based phenomena, and connect verses about nature with the scientific processes they observe. Exploratory activities recorded the highest average engagement rate of 71%, while the ability to connect verses with phenomena reached 55.5%. In addition to improving cognitive skills, this approach also strengthens students’ scientific and religious attitudes, such as accuracy, curiosity, and awareness that natural phenomena are signs of God’s power. This study concludes that scientific interpretation is a potential approach to improve scientific literacy while building students’ scientific spirituality. However, the success of its implementation still depends on teacher competence and the availability of adequate experimental media. These findings have important implications for curriculum development and for teacher training in Islamic education.